2018
DOI: 10.1016/j.geoderma.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate and glyphosate sorption in soils following long-term phosphate applications

Abstract: Phosphate and glyphosate molecules compete for sorption sites in soil. The objective of this study was to quantify the impact of Olsen P concentrations in two contrasting soils on phosphate and glyphosate sorption. Soils were a sandy clay loam soil rich in iron oxides (SCL-Fe 2 O 3) and a clay loam soil rich in calcium carbonates (CL-CaCO 3). The phosphate Freundlich sorption coefficient (K f) ranged from 3 to 68 L 1/n mg 1-1/n kg-1 in the SCL-Fe 2 O 3 and from 21 to 76 L 1/n mg 1-1/n kg-1 in the CL-CaCO 3. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 54 publications
9
14
1
1
Order By: Relevance
“…This suggests significant competition between GPS and PO 4 ions for reactive sites in both matrices, with PO 4 being preferentially sorbed. These results are consistent with studies investigating competitive sorption between GPS and PO 4 by soils (de Jonge et al, 2001; Munira et al, 2016, 2018). Although GPS sorption decreased in the presence of PO 4 , both soils exhibited relatively high affinities for solvated GPS.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests significant competition between GPS and PO 4 ions for reactive sites in both matrices, with PO 4 being preferentially sorbed. These results are consistent with studies investigating competitive sorption between GPS and PO 4 by soils (de Jonge et al, 2001; Munira et al, 2016, 2018). Although GPS sorption decreased in the presence of PO 4 , both soils exhibited relatively high affinities for solvated GPS.…”
Section: Resultssupporting
confidence: 92%
“…Several studies demonstrated that GPS sorption by soils decreased in the presence of PO 4 . Studying the effect of field-aged P on GPS sorption, de Jonge et al (2001) reported reductions of Freundlich partitioning coefficients as much as 50% in soils with the greatest contents of Olsen P, relative to soils with the lowest concentrations of Olsen P. A similar finding was reported by Munira et al (2016) where linear partitioning coefficients were reduced by 25 to 44% in soils with high concentrations of Olsen P relative to control soils, consistent with findings from a more recent study (Munira et al, 2018). Additionally, Kanissery et al (2015) found that GPS sorption was significantly decreased by PO 4 addition under both oxic and anoxic conditions.…”
Section: Introductionsupporting
confidence: 84%
“…Only a few field studies have been conducted to study the effect of soil amendment on crop grain concentrations of heavy metals cultivated in contaminated soils (Rehman et al 2015) Most soils in northern China are calcareous. In calcareous soils, the added soluble phosphate ions may react with Ca and Mg ions resulting in less soluble phosphates and makes phosphorus fertilizer less available to plants over time (Munira et al 2018;Zhu et al 2018). In order to decrease the reaction between phosphate ions from fertilizer and the Ca, Mg ions in soil, it is recommended that band application is employed for P fertilizer application (Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate and Pb ions have poor mobility in soil (Stecker et al 2001). This is truer in calcareous contaminated soils, where the added phosphate ions from P fertilizers reacts with cations like Pb, Ca and Mg (Munira et al 2018;Zhu et al 2018). The concentration of Ca is often much higher than that of Pb in most soils; even contaminated soils.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate was previously considered to be a safe, environmentally friendly herbicide because of its rapid adsorption onto soil particles. Usually, glyphosate residues in agricultural soils are mobilised off-site by wind and water-erosion than by runoff or leaching [7]. But studies have found that glyphosate may become portable by water in soils with high phosphate levels.…”
Section: Table 23 Change In the Share Of Total Glyphosate As The Actmentioning
confidence: 99%